Predicting Reading Comprehension: The Role of Schemata and Reading Motivation - La Kooko; Kamaluddin Kamaluddin; Alberth Alberth (Halu Oleo University, 2023)
This study has three primary objectives: (a) to examine the individual contributions of predictors to reading comprehension; (b) to explore the combined influence of multiple factors on reading comprehension (c) to identify which predictors have a significant impact on reading comprehension. Conducted at SMA Negeri 1 Gu, Central Buton Regency, this research employed a quantitative approach to assess both the individual and collective effects of various factors on reading comprehension among 151 twelfth-grade students. Regression analysis was utilized to gauge the extent of these factors' impact. The findings indicate that schema variables significantly affect reading comprehension, as evidenced by a significance value (sig) of 0.000, surpassing the threshold of 0.005, along with a t-test value of -14.339, exceeding the critical t-table value of 1.9763. Similarly, there is a notable relationship between reading motivation variables and reading comprehension, with a sig value of 0.000 and a t-test value of 5.965, both exceeding the respective thresholds. These outcomes offer valuable insights for educators, suggesting avenues for enhancing students' reading comprehension through tailored instructional strategies aligned with their individual abilities.